Penerapan Digital Signature Untuk Identitas File Audio Dengan Metode Snefru - Fajri, Muhammad (Management of Information System Journal, 2022)
In the era of information technology that is developing very rapidly, the use of signatures has been widely applied digitally through digital signatures. Digital signatures along with the times have led to the need for authentication of data or files that are used digitally. Its use also aims to avoid counterfeiting or interference. Currently, the use of digital signatures has been widely applied to software distribution, financial transactions, file transfers. The crime of falsifying audio files is a serious problem in various fields. Audio authenticity testing is important and significant in all social areas, especially when audio is used as evidence for conclusions in courts, the basis for judicial decision-making, and corporate reports. Forgery of audio files will cause losses that cannot be estimated. One solution to the problems mentioned above is to perform the process of assigning an identity to the audio file, so that it can be seen that the audio cannot be manipulated. The SNEFRU method is a hash function to detect changes in digital audio. SNEFRU has several variants, varying in number of operands and hash size. The supported hash sizes are 128 and 256 bits. The number of passes in the final 2-pass variant source of SNEFRU is two passes, while a more secure 4-pass version is also available. After the previous attack was published, the 8-pass version was introduced as well. This 8-pass version is still considered safe.